Causes of Death After Colorectal Cancer Diagnosis: A Population-Based Study - Feng, Yuqian; Jin, Huimin; Guo, Kaibo; Wasan, Harpreet S.; Ruan, Shanming; Chen, Cihui (Frontiers in Oncology, 2021)
Background: Non-cancer causes of colorectal cancer (CRC) death have not received much attention now. The current study has been to study the non-caner causes of death in CRC patients at different latency periods. Methods: Eligible CRC patients were included from Surveillance, Epidemiology, and End Results (SEER) database and standardized mortality ratios (SMRs) were calculated using SEER*Stat 8.3.8. Results: A total of 475,771 patients with CRC were included, of whom 230,841 patients died during the follow-up period. Within 5 years, CRC was the leading cause of death. Over time, non-cancer causes of death account for an increasing proportion. When followed for more than 10 years, non-cancer deaths accounted for 71.9%. Cardiovascular diseases were the most common causes of non-cancer deaths, accounting for 15.4% of the total mortality. Patients had a statistically significant higher risk of death from septicemia within the first year after diagnosis compared with the general population (SMR, 3.39; 95% CI, 3.11-3.69). Within 5 to 10 years after CRC diagnosis, patients had a statistically significant higher risk of death from diabetes mellitus (SMR, 1.27; 95% CI, 1.19-1.36). With time more than 10 years, patients with CRC had a statistically significant higher risk of death from atherosclerosis (SMR 1.47; 95% CI, 1.11-1.9). Conclusions: Although CRC has always been the leading cause of death in CRC patients, non-cancer causes of death should not be ignored. For cancer patients, we should not only focus on anti-tumor therapy, but also evaluate the occurrence of other risks to prevent and manage it in advance.